Pengaruh Profitabilitas, Ukuran Perusahaan, dan Leverage Terhadap Perataan Laba pada Perusahaan Manufaktur di BEI - Tria Oktaviasari; Muhammad Miqdad; Rochman Effendi (UPT Penerbitan Universitas Jember, 2018)
This research aims to determine the effect of profitability, company size, and leverage on income smoothing. This research used secondary data obtained from the Indonesia Stock Exchange in 2011 to 2015. Methods of data analysis using descriptive statistics, Classical Assumption Test, and Hypothesis Testing consists of Multiple Linear Regression method, F test, t test, and coefficient of determination. The results showed a significant relationship between profitability, company size, and leverage on income smoothing. This result proves that profitability, company size, and leverage able to give effect to the income smoothing. Income smoothing conducted to showed the stability of the company's profit in each period so that will increase the interest of investors to invest.Keywords: Income smoothing, profitability, size of company, Leverage